Penggunaan Matriks SWOT dan Metode QSPM pada Strategi Pemasaran Jasa Wedding Organizer: Studi Kasus pada UMKM Gosimplywedding Sukabumi - Dicki Prayudi; Resti Yulistria (Jurnal Maksipreneur, 2020)
Wedding Organizer (WO) is one of the service business sectors to prepare wedding events. Since its establishment in 2015, a Small and Medium Enterprise (SME) namely Gosimplywedding (Gosimply) has not formulated a marketing strategy in line with the condition of the company. This research objective is to measure internal and external company environment scores in determining the position of Gosimply as a business unit of SME to formulate its business strategies. This analysis uses the SWOT (Strength, Weakness, Threat, Opportunity) matrix mapping and QSPM (Quantitative Strategic Planning Matrix) analysis to find out the results of the calculation in the company environment to know what are the strengths, weaknesses, opportunities, and threats faced by the company. In 2019, the QSPM method becomes the most choice to measure the extent of the internal and external strengths of Gosimply to formulate its marketing strategies. The results of this research showed that the final weighting score in the internal analysis is the strength in its organizational flows and the weakness is the character of its human resources. The weighting in the external aspect as the company’s opportunity is the demographic of the people who need its product, while the most company threat is the number of competitors and STP (Segmenting, Targeting, and Positioning) of the product. The integration of the internal and external aspects of the company environment into the SWOT Matrix results in the strategy of growth in the concentration of horizontal integration.